Italian ma ‘but’ in deverbal pragmatic markers: Forms, functions, and productivity of a pragma-dyad - Fedriani, Chiara; Molinelli, Piera (Cuadernos de Filología Italiana, 2019)
This paper focuses on the development, paradigmaticization, and productivity of a set of complex pragmatic markers in Italian, which are constituted by two distinct elements, namely the adversative conjunction ma ‘but’ and a deverbal pragmatic marker (e.g., ma dai ‘come on! really!’, literally: ‘but give’, or ma piantala ‘just stop! give it a rest!’, literally ‘but dump it’). The main idea we will develop is that such a complex pattern can be better described in terms of a pragma-dyad, i.e., a dyadic construction with a pragmatic meaning, featuring a fixed element which systematically combines with a set of preferential fillers. In our case, the fixed element is ma, which generally signals a contrast with the interlocutors’ point of view, thus shaping the pragmatic meaning of the resulting complex in terms of interactional contrast. Such a meaning is then functionally enriched through a variety of fillers compatible with the schema, which actualize it in conveying mock politeness, disagreement, counter-expectation, and pragmatically neighbouring values. By providing a corpus-based study of the development and productivity of these complex markers, we illustrate the empirical and theoretical advantages which a pragma-dyadic approach can offer in exploring processes of functional enrichment involving complex markers.